Integrating toda embroidery with pre-consumer textile waste: A sustainable approach to fashion production and cultural preservation - Ramya Arivanantham; Vineeth Radhakrishnan (MethodsX, 2025)
This research aims to develop a systematic approach for reducing pre-consumer textile waste by integrating traditional Toda embroidery techniques into garment repair. This study focuses on promoting environmental sustainability while preserving indigenous cultural heritage. Drawing parallels with the Japanese Kintsugi concept, which transforms broken ceramics into aesthetic enhancements, this study proposes a structured method to elevate defective textiles through Indigenous craftsmanship. The Sustainable Textile Repair through Indigenous Embroidery (STRIE) Method consists of four phases, i) Defect Assessment ii) Artisan Engagement iii) Repair Execution and iv) Quality Assurance. This framework extends garment lifespans, reduces environmental impact and creates sustainable economic opportunities for Toda artisans. The STRIE Method presents a scalable framework for sustainable textile repair, strategically aligning with four United Nations Sustainable Development Goals (SDGs 8, 11, 12, 13). This innovative strategy facilitates the conversion of textile waste into garments that carry cultural significance while promoting environmental sustainability. It adeptly fuses traditional craftsmanship with modern sustainable production techniques, creating a model that enhances both the ecological and cultural value of textile products. • Introduces a structured integration of traditional craftsmanship into modern repair. • Combines digital defect assessment with artisan training and quality assurance. • Reduces textile waste, preserves cultural heritage and supports sustainable livelihoods.